Högt och lågt i skandinaviska dialekter - Riad, Tomas (Scandinavistica Vilnensis, 2014)
The typology of Scandinavian dialects is based on prosodic features, namely tone and intonation. We look at three variables that account for the variation between the large dialect groups: 1. The value of the lexical tone in accent 2, 2. Whether there is one or two association points for the tonal contour in compounds, and 3. Whether there is spreading or interpolation between the lexical tone and the prominence tone in compounds. The relevance of these variables is illustrated by comparisons of real pronunciations from several dialects, including Olso (East Norwegian), Göteborg (West Swedish), Stockholm (Central Swedish), Norberg (Dala Swedish), Skåne (South Swedish), and Luleå (North Swedish).